Homologous series of n-alkanes (C19-C35), fatty acids (C12-C32) and n-alcohols (C8-C30) in atmospheric aerosols from central Alaska: Molecular distributions, seasonality and source indices. (July 2018) - Boreddy, Suresh K.R.; Haque, Md. Mozammel; Kawamura, Kimitaka; Fu, Pingqing; Kim, Yongwon
Abstract: To better understand the molecular distributions, seasonality and source indices of organic aerosols in central Alaska, we measured homologous series of n-alkanes (C19 -C35 ), fatty acids (C12 -C32 ) and n-alcohols (C8 -C30 ) in total suspended aerosols collected during June 2008 to 2009 using a gas chromatography/mass spectrometry (GC-MS). The whole sampling period was divided as warm (early May to late September; summer) and cold (late September to early May; winter) periods. Molecular distribution was characterized in both periods by the predominance of C25 for n-alkanes and C24:0 for fatty acids. However, we noticed a difference in molecular distribution of n-alcohols between warm and cold periods, which was characterized by the predominance of C22 in warm season while C26 in cold period. Except for fatty acids, n-alkanes and n-alcohols showed higher concentrations in warm period than in cold period. We found significantly higher ratios of C18:1 /C18:0 in warm period than those in cold period, suggesting the fresh biogenic and aged anthropogenic aerosols in warm and cold periods, respectively. This inference was consistent with significantly higher ratios of WSOC/OC, a proxy for photochemical aging, in cold period. Based on the carbon preference index (CPI), average chain length (ACL), low-to-high molecular weight (LMW/HMW) ratios, wax n-alkanes (%WNA) and estimated fossil fuel concentrations, we demonstrate that higher plant waxes, biomass burning from wildfires are two important sources in warm period while combustion derived anthropogenic emissions are major sources in cold period in central Alaska. This finding was further supported by higher ratios of nss-K + /elemental carbon (EC) and methanesulfonate (MSA − )/EC ratios in warm period. Highlights: Sources and atmospheric abundance of lipid class compounds were determined in aerosols in central Alaska. Mean concentrations of all lipids were significantly higher in warm period. Higher plant waxes, biomass burning emissions from wildfires are major sources in warm period. Combustion derived anthropogenic sources important in cold period.